2001
DOI: 10.1029/2001ja900118
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machine as an efficient tool for high‐dimensional data processing: Application to substorm forecasting

Abstract: Abstract. The support vector machine (SVM) has been used to model solar wind-driven geomagnetic substorm activity characterized by the auroral electrojet (AE) index. The focus of the present study, which is the first application of the SVM to space physics problems, is reliable prediction of large-amplitude substorm events from solar wind and interplanetary magnetic field data. This forecasting problem is important for many practical applications as well as for further understanding of the overall substorm dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…(4) It avoids traps by local minima. In space physics, SVM has been used in forecasting, including solar F 10.7 [ Huang et al , ], solar wind velocity [ Liu et al , ], substorms [ Gavrishchaka and Ganguli , ], Kp [ Ji et al , ], and storm time ionosphere [ Sun et al , ]. SVRM has been applied to model the magnetopause shape [ Wang et al , ].…”
Section: Regression Analysismentioning
confidence: 99%
“…(4) It avoids traps by local minima. In space physics, SVM has been used in forecasting, including solar F 10.7 [ Huang et al , ], solar wind velocity [ Liu et al , ], substorms [ Gavrishchaka and Ganguli , ], Kp [ Ji et al , ], and storm time ionosphere [ Sun et al , ]. SVRM has been applied to model the magnetopause shape [ Wang et al , ].…”
Section: Regression Analysismentioning
confidence: 99%
“…Machine learning can automatically make a model from data, even in case that they are not clearly understood. Therefore machine learning technology has been employed for space weather applications in the following two aspects: space weather prediction (Al-Omari et al 2010;Chen et al 2010;Colak et al 2009;Gavrishchaka et al 2001;He et al 2008;Li et al 2007;Liu Corresponding Author : Y.-J. Moon et al 2011;Olmedo et al 2005;Qahwaji et al 2007Qahwaji et al , 2008Yuan et al 2011) and solar feature identification (Henwood et al 2010;Labrosse et al 2010;Quaalude et al 2003Quaalude et al , 2005Martens et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Once the kernel function is chosen, kernel representation allows one to learn effectively by choosing the underlying map and dimension N (Gavrishchaka and Ganguli, 2001).…”
Section: Brief Review On the Support Vector Machinementioning
confidence: 99%
“…It is found that this method provides a good compromise between the model complexity and learning ability, when there is limited input data. In particular, we note that Gavrishchaka and Ganguli (2001) used an SVM to model solar wind-driven geomagnetic substorm activity characterized by the auroral electrojet (AE) index. Qahwaji and Colak (2007) compared several machine learning algorithms for an automated short-term solar flare prediction and found that SVMs have the best performance for predicting whether a McIntosh classified sunspot group is going to flare or not.…”
Section: Introductionmentioning
confidence: 99%